Photophysical and photoconductivity properties of thiol-functionalized graphene-CdSe QD composites - Debgupta, Joyashish; Mandal, Sadananda; Kalita, Hemen; Aslam, Mohammed; Patra, Amitava; Pillai, Vijayamohanan (RSC Advances, 2014)
Graphene-semiconductor QD hybrid nanostructure materials have recently emerged as a new class of functional materials because of their potential applications in solar energy conversion, optoelectronic devices, sensing etc. Here, oleic acid-capped CdSe QDs are attached to -PhSH functionalized graphene by ligand exchange via bonding with the -SH group. The shifting of the G-band and D-band due to structural changes for the attachment of QD with graphene has been evaluated by using Raman spectroscopy. Steady state photoluminescence (PL) and time resolved fluorescence measurements have been employed to understand the electronic interactions between graphene and CdSe QDs. A time resolved fluorescence spectroscopic study has been used to understand the fluorescence dynamics of the photoexcitated CdSe QDs in the presence of graphene. It is evident that the electron transfer occurs from photoexcited QDs to graphene and the electron transfer rate is found to be 12.8 x 10(8) s(-1) for 3.8 nm CdSe QDs. Photoconductivity properties of the graphene-QD device under illumination have been examined and it is to be noted that 2-3 fold increase in the photocurrent is found in this composite device in presence of 1.5 AM solar simulated light. The enhancement of the photocurrent in this hybrid device is found to be suitable for potential applications in optoelectronic and solar cell systems.